Estudio dogmático jurídico sobre la proporcionalidad de la pena del delito de femicidio en el COIP. - Pazmiño Secaira, Dina Esmeralda (2022)
The objective of this research is to carry out a legal dogmatic study on the proportionality of the penalty for the crime of femicide in the Organic Integral Penal Code. For this purpose, a methodology is used that starts with a conceptual review of the criminal law of a bibliographic and documentary nature, towards the descriptive methods of the concepts of the principle of proportionality and the crime of femicide, in order to compare the relationship between them, to subsequently determine whether the principle of proportionality is applied at the time of punishing the crime under study; through structured questionnaires and surveys to a sample of one hundred and four law professionals in the province of Bolivar, who provide information on the problem raised. The results decide that in Ecuador there is a basic idea of the gender criterion with which to act, both the administrators of justice and the administered, who understand the principle of proportionality as a relevant criterion when punishing offenders of femicide crimes. This research is an important study, because femicide is a social problem that requires a revision of the legal principles not with normative changes, but in its form of execution.